Anthelmintic efficacy of oral trichlorfon solution against ivermectin resistant nematode strains in cattle - Zanetti Lopes, Welber Daniel [UNESP]; dos Santos, Thais Rabelo [UNESP]; Borges, Fernando de Almeida [UNESP]; Sakamoto, Claudio A. M. [UNESP]; Soares, Vando Edesio [UNESP]; Nogueira Costa, Gustavo Henrique [UNESP]; Camargo, Gilberto; Pulga, Mario Eduardo; Bhushan, Chandra; da Costa, Alvimar Jose [UNESP] (Elsevier B.V., 2009)
Infected calves from two different rural estates in Brazil were studied to assess the anthelmintic efficacy of oral trichlorfon against naturally occurring ivermectin resistant parasitic nematode strains. In experiment 1, infected animals were from a region where ivermectin resistant populations of Haemoncus placei, Cooperia punctata,Cooperia spatulata and Trichuris discolor have recently been identified. Six calves with natural gastrointestinal nematode infections were treated with 48.5 mg/kg aqueous trichlorfon administered orally and six calves acted as a non-treated control group. In experiment 11 24 naturally infected calves were selected to enter one of four treatment groups, six animals each received: 48.5 mg/kg oral trichlorfon; 200 mu g/kg subcutaneous 1% ivermectin; 630 mu g/kg subcutaneous 3.15% ivermectin; or no treatment (control group). Gastrointestinal helminths were counted and identified post-mortem at 7 days (trichlorfon and 1% ivermectin treated and untreated animals) or 14 days (3.15% ivermectin treated and untreated animals) after administration of the test agents. Experiment I identified a high level efficacy for oral trichlorfon against four helminth species that have previously been shown to be ivermectin resistant in this geographical region: percentage efficacy was 99.82% against adult H. placei, 99.18% against C. punctata, 99.33% against C. spatulata, 81.06% against T. axei, 98.46% against Oesophagostomum radiatum and 100% against T. discolor. Trichlorfon also showed activity against the ivermectin (1% and 3.15%) resistant helminth species identified in experiment 11, attaining efficacy levels of 99.17% against H. placei, 98.46% against C punctata and 100.00% against T. discolor. These findings indicate that oral trichlorfon is an effective treatment option in the management of cattle infected with ivermectin resistant helminths. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cattle; Helminth; Macrocyclic lactones; Ivermectin resistance